Comparison of viscoelastic finite element models for laminated glass beams. (October 2017) - Zemanová, Alena; Zeman, Jan; Šejnoha, Michal
Highlights: Four different layer-wise formulations suitable for modeling of non-linear behavior of laminated glass beams with viscoelastic interlayer have been introduced and compared. The formulations differ in the beam theory adopted at the layer level (von Kármán/Reissner) and in the constitutive law for the interlayer (temperature-sensitive viscoelasticity with timeindependent bulk modulus/Poisson ratio). For both fixed-end and simply-supported beams, it has been shown that the four formulations provide very close results. The most straightforward formulation, based on the von Kármán model and the constant Poisson ratio assumption, has been thoroughly verified against two-dimensional finite element simulations and partially validated against experimental data. Graphical abstract: Abstract: Laminated glass elements, which consist of stiff elastic glass layers connected with a compliant viscoelastic polymer foil, exhibit geometrically non-linear and time/temperature-sensitive behavior. In computational modeling, the viscoelastic effects are often neglected or a detailed continuum formulation typically based on the volumetric-deviatoric elastic-viscoelastic split is used for the interlayer. Four layerwise beam theories are introduced in this paper, which differ in the non-linear beam formulation at the layer level (von Kármán/Reissner) and in constitutive assumptions for the interlayer (a viscoelastic solid with the time-independent bulk modulus/Poisson ratio). We perform detailed verification and validation studies at different temperatures and compare the accuracy of the selected formulation with simplified elastic solutions used in practice. We show that all the four formulations predict very similar responses. Therefore, our suggestion is to use the most straightforward formulation that combines the von Kármán model with the assumption of time-independent Poisson ratio. The simplified elastic model mostly provides response in satisfactory agreement with full viscoelastic solutions. However, it can lead to unsafe or inaccurate predictions for rapid changes of loading. These findings provide a suitable basis for extensions towards laminated plates and glass layer fracture, owing to the modular format of layerwise theories.